Risk factors for dots treatment default among new HIV-TB coinfected patients in Nalgonda (Dist.) Telangana (State): A case control study - Siva Balaji Reddy Satti; Nagaraj Kondagunta (Wolters Kluwer Medknow Publications, 2016)
Background: The therapeutic regimens as recommended by the Revised National TB Control Programme (RNTCP) have been shown to be highly effective for both preventing and treating tuberculosis, but poor adherence to medication is a major barrier to its global control. Aim and Objectives: The study was conducted to assess the influence of patient related factors for DOTS Treatment Default among HIV-TB Co-infected cases. Setting and Design: This was a case control study conducted in Nalgond, Telangana. Materials and Methods: All new HIV-TB coinfected and DOTS-defaulted patients registered under RNTCP for the period from January 2010 to December 2012 were selected. Of the 154 patients, 23 had died and 11 could not be traced, and these were excluded. Thus the total number of available cases were 120 for those age- and sex-matched controls (HIV-TB coinfected patients and those who had completed the DOTS regimen successfully) were selected. Results: The mean age was 36.5 ± 9 years; the majority (23.3%) of patients defaulted during the second month of treatment. Significant risk factors associated with defaulting included unskilled occupation [adjusted odds ratio (AOR: 3.56; 95% confidence interval (CI): 1.1-11.56], lower middle class socioeconomic status (AOR: 17.16; 95% CI: 3.93-74.82), small family size (AOR: 21.3; 95% CI: 6.4-70.91), marital disharmony (AOR: 6.78; 95% CI: 1.93-23.76), not being satisfied with the conduct of health personnel (AOR: 7.38; 95% CI: 2.32-23.39), smoking (AOR: 8.5; 95% CI: 2.31-31.21), and side effects of drugs (AOR: 4.18; 95% CI: 1.35-12.9). Conclusion: Unskilled occupation, marital disharmony, small family size, lower middle class socioeconomic status, not being satisfied with the conduct of health personnel, smoking, and drug side effects were significantly associated with defaulting. Information on the pattern of tuberculosis (TB), the outcome of anti-tuberculosis treatment (ATT), and the factors associated with it will help in planning interventions to improve adherence to DOTS treatment.